Prevalence of Soil Transmitted Helminths in Elementary School Students with Behavioral Risk Factors - Sapada, Ibrahim Edy; Asmalinda, Wita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
The high prevalence of Soil-Transmitted Helminths (STH) infection cases is due to several complementary risk factors, including tropical climate factors which provide ideal conditions for the development of worm eggs, unhealthy living behavior factors including defecation habits, eating habits and wearing bedding. feet, not washing hands, not cutting nails regularly. The purpose of this study was to determine the correlation between the prevalence of Soil-Transmitted Helminths (STH) infection with behavioral risk factors in school children. This type of research is an analytical epidemiological study in two different areas. The research design used was a cross-sectional study. This research was conducted in Bukit Village and Srikembang Village, Betung District, Banyuasin Regency, South Sumatra for 30 days. The research sample was 252 children. Data analysis showed that the type of STH with the highest prevalence in SDN 1 Bukit was A. lumbricoides, while at SDN 1 Sri Kembang was T. trichiura. It can be concluded that the supporting factors for transmission in the two research locations were the habit of washing hands before eating, the habit of children playing in the garden/field, the habit of cutting nails, the habit of defecating, the habit of wearing footwear while playing/working. It is suggested to do further research with environmental risk factor variables.Abstrak: Tingginya prevalensi kasus infeksi Soil Transmitted Helminths (STH) dikarenakan oleh beberapa faktor resiko yang saling melengkapi, antara lain faktor iklim tropis yang menyediakan kondisi ideal bagi perkembangan telur-telur cacing, faktor perilaku hidup yang kurang sehat meliputi kebiasaan defekasi, cara makan dan pemakaian alas kaki, tidak mencuci tangan, tidak rutin memotong kuku. Tujuan penelitian ini adalah untuk mengetahui korelasi antara prevalensi infeksi Soil Transmitted Helminths STH dengan faktor resiko perilaku pada anak sekolah. Jenis penelitian ini adalah studi epidemiologi secara analitik di dua daerah yang berbeda. Desain penelitian yang digunakan adalah potong lintang (cross sectional study).  Penelitian ini dilakukan di Desa Bukit dan Desa Srikembang Kecamatan Betung Kabupaten Banyuasin Sumatera Selatan selama 30 hari. Sampel penelitian adalah murid SDN sebanyak 252 orang. Analisis data didapatkan Jenis STH dengan prevalensi tertinggi di SDN 1 Bukit adalah A. lumbricoides,  sedangkan di SDN 1 Sri Kembang adalah T. trichiura. Dapat disimpulkan bahwa faktor pendukung transmisi di kedua lokasi penelitian adalah, kebiasaan cuci tangan sebelum makan, kebiasaan anak-anak bermain di kebun/lading, kebiasaan potong kuku, kebiasaan buang air besar, kebiasaan memakai alas kaki saat bermain/bekerja. Disarankan untuk dilakukan penelitian lebih lanjut pada dengan variable faktor resiko lingkungan.